Humoral Immunity to Measles, Mumps, Rubella, Diphtheria, Tetanus and Pertussis After Cancer Treatment in Children - Susanna Sundell; Miia Laine; Liisa Järvelä; Ville Peltola; Tytti Vuorinen; Päivi Lähteenmäki; Linnea Schuez‐Havupalo (Cancer Reports)
ABSTRACT Background Treatment for pediatric malignancies has distinct effects on the immune system. Aims Our aim was to measure humoral immunity to measles, mumps and rubella (MMR), and diphtheria, tetanus and acellular pertussis (DTaP) vaccines after pediatric cancer treatment. Method We assessed IgG titers of 52 children against the vaccine antigens post‐treatment. Results After completed primary vaccination series for MMR and DTaP before treatment, post‐treatment there was a considerable proportion of patients with below‐reference titers against pertussis, diphtheria and tetanus, but only few subjects showed below‐reference titers against measles, mumps and rubella. Our findings may have implications when considering re‐vaccination policies.